Given a n = { 1 , 2 , 2 , 3 , 3 , 3 , 4 , 4 , 4 , 4 , 5 , 5 , 5 , 5 , 5 , 6 , 6 , 6 , 6 , 6 , 6 , 7 , . . . }
Find a 2 0 1 6 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
When taking floor functions, we cannot just discard fractional parts, especially when they are multiplied by a large number. That explains why you have an error of 0.5 (see comments for more details).
More accurately, if a n = k , then we have
2 ( k − 1 ) 2 + ( k − 1 ) < n ≤ 2 k 2 + k
This gives us
( k − 1 ) 2 + ( k − 1 ) + 4 1 < 2 n + 4 1 ≤ k 2 + k + 4 1
or that
( k − 1 + 2 1 ) < 2 n + 4 1 ≤ k + 2 1
This explains where you were "off by 0.5".
The conclusion is that a n = ⌈ 2 n + 4 1 − 2 1 ⌉ .
Log in to reply
I had never seen your reply but it makes much more sense now, thank you!!
Log in to reply
Check your email settings. You should have received an email when a Challenge Master leaves a note on your solution, and also when anyone comments/replies to you.
Problem Loading...
Note Loading...
Set Loading...
If the first few terms are listed, a pattern can be noticed (besides the obvious one that each term n occurs n times):
a 1 = 1 a 2 = 2 a 3 = 2 a 4 = 3 a 5 = 3 a 6 = 3 a 7 = 4 a 8 = 4 a 9 = 4 a 1 0 = 4
Seeing how there seems to be a pattern where each term stops repeating (1,3,6,10,...). We can define a second sequence, b n , that tells us the nth term where n stops repeating; b n = ∑ k = 1 n k = 2 n ( n + 1 ) . (For example, b 3 = 6 and b 4 = 1 0 ).
Now, if we were to take the inverse of b n , it would actually output instead what term n is in the midst of being repeated at the nth term, so given some manipulation:
n = 2 a n ( a n + 1 ) 2 n = a n ( a n + 1 ) ⌊ 2 n ⌋ = ⌊ a n 1 + a n 1 ⌋ a n = ⌊ 2 n ⌋
(Upon checking a table for accuracy, it was off by .5, so then a translation was made to correct the error, although personally I'm not sure where the error came up.)
a n = ⌊ 2 n + 2 1 ⌋ a 2 0 1 6 = 6 3 .